Using netmeeting in synchronous teaching and learning of mathematics for UiTMs students / Ling Siew Eng ... [et al.] - Ling, Siew Eng; Mahdi, Rasidah; Chen, Chee Khium (2011)
Over the past two decades, the advancement of technology has given different perspective to the teaching and learning approach. It has enhanced the teaching and learning by providing a flexible approach to capture the learner's attention, motivation and at the same time provide ample opportunities for independent study over a click of a mouse. Educators have no choice but to move along with these waves of change so that their teaching approaches are relevant and current. It is believe that good teaching approaches with the help of appropriate tools can improve better understanding in the teaching and learning process. Hence, incorporating technology in the teaching and learning is a must. However, to come up with an appropriate tool is not that simple. There are many technology tools being developed and the fact that certain technology tool is developed for a specific purpose makes the choice more difficult. Therefore, when a certain technology tool is chosen to enhance the teaching and learning approach, a proper study needs to be conducted to assess its effectiveness and challenges prior to its implementation.